Efektivitas Pelatihan Emotional Intelligence untuk Meningkatkan Resiliensi pada Siswi SMP yang Melakukan Self Injury - Lebda Katodhia; Frikson C. Sinambela (Universitas Islam Tribakti Lirboyo Kediri, 2020)
The rise of the case of middle school students who commit acts of self-injury creates new problems in education. The cause is a lack of resilience in self. When this condition is left constantly, it will have an impact on psychological problems. This study aims to understand the effectiveness of emotional intelligence training in enhancing students’ resilience in SMP X Surabaya. The method used in this experimental study is a single case experimental design. There were 19 female students have been doing self-injury such as slashing their hands. First, The Resilience Scale is used to assess students’ resilience and The Assessing Emotions Scale Mayor-Salovey is used for assessing emotional intelligence. Second, the result analyzed with Paired Sample T-test. Third, Linear Regression Analysis conducted to examine the effect the training on students’ resiliency. In the follow-up stage, the data analyzed using a Wilcoxon Signed Rank. The emotional intelligence training gave in 4 sessions within 2 days. Besides, in the follow-up stage, participants are interviewed. The result shows statistical significance of 0.009 (p < 0.05). It conveys there is a significant difference in students' resilience levels before and after the training. The significant results of the training lasted until the follow-up one week after the training. The existence of emotional intelligence makes the participants more persistent and resilient in dealing with daily problems so that the participants will not repeat their self-harming behavior.